2011
DOI: 10.1371/journal.pone.0027745
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitivity of Genome-Wide-Association Signals to Phenotyping Strategy: The PROP-TAS2R38 Taste Association as a Benchmark

Abstract: Natural genetic variation can have a pronounced influence on human taste perception, which in turn may influence food preference and dietary choice. Genome-wide association studies represent a powerful tool to understand this influence. To help optimize the design of future genome-wide-association studies on human taste perception we have used the well-known TAS2R38-PROP association as a tool to determine the relative power and efficiency of different phenotyping and data-analysis strategies. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 37 publications
(49 reference statements)
5
48
1
Order By: Relevance
“…Some recent reports have shown no relationships between gustin polymorphisms and PROP tasting or papillae density in geneticallydiverse cohorts. Specifically, Genick et al [50] found no relationship between gustin and PROP phenotypes in a genome-wide association study conducted in Brazil [50]. Likewise, Feeney & Hayes [51] reported no associations between 12 selected polymorphisms in the gustin gene and PROP bitterness or papillae density in a U.S. cohort.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some recent reports have shown no relationships between gustin polymorphisms and PROP tasting or papillae density in geneticallydiverse cohorts. Specifically, Genick et al [50] found no relationship between gustin and PROP phenotypes in a genome-wide association study conducted in Brazil [50]. Likewise, Feeney & Hayes [51] reported no associations between 12 selected polymorphisms in the gustin gene and PROP bitterness or papillae density in a U.S. cohort.…”
Section: Discussionmentioning
confidence: 98%
“…However, two recent studies in ethnically-mixed populations in Brazil [50] and the U.S. [51] failed to find associations between PROP tasting and gustin genotypes. The aim of this study was to confirm the role of the gustin gene polymorphism in PROP sensitivity and fungiform papilla density in an ethnically-mixed sample, and to identify confounding factors which may explain discrepant findings for gustin gene effects across populations.…”
mentioning
confidence: 92%
“…We reasoned that perhaps combining biological with behavioral approaches would enable us to better understand FV intake and obesity. The chemical propylthiouracil (abbreviated as PROP) is found in brassica or cruciferous vegetables; it accounts for any bitter taste when eating them, and the ability to taste the bitterness from PROP is genetically determined [45]. Some research had shown that individuals who could taste PROP were less likely to eat these vegetables, and more likely to be obese.…”
Section: Mediating Variables: Influences On Behaviormentioning
confidence: 99%
“…In one of our recent studies, we carried out a GWAS with urine metabolic traits in a cohort of 265 subjects from the general population of the São Paulo metropolitan area of Brazil (Galindo-Cuspinera et al 2009;Genick et al 2011). …”
Section: Replication Of Gene-metabolism Associationsmentioning
confidence: 99%